Enzyme Replacement Therapy with Idursulfase in Patients with Mucopolysaccharidosis Type II: Literature Review - Nato D. Vashakmadze; Natalya V. Zhurkova; Olga B. Gordeeva; Elena V. Komarova; Tatyana E. Privalova; Anastasya I. Rykunova; Marina А. Babaykina (Вопросы современной педиатрии)
Mucopolysaccharidosis type II (MPS II; Hunter syndrome) is X-linked hereditary disease from the group of lysosomal storage disease. Its prevalence is 3–7 cases per 1 million live-born boys. MPS II occurs due to the deficiency of iduronate-2-sulfatase enzyme because of pathological changes in the structure of the IDS gene. Enzyme deficiency leads to the accumulation of glycosaminoglycans (GAGs), dermatan sulfate and heparan sulfate, in lysosomes. This leads to the damage of various organs and systems in the body with further development of clinical picture of the disease: coarse face, recurrent infections of upper respiratory tract, hearing loss up to deafness, cardiovascular and respiratory systems pathologies, hepatosplenomegaly, musculoskeletal system abnormalities, low growth, central nervous system damage. Enzyme replacement therapy with idursulfase, that was introduced in clinical practice 15 years ago, has significantly changed the quality of life of these patients. Idursulfase is purified form of natural lysosomal enzyme iduronate-2-sulfatase obtained via human cell line. Exogenous enzyme entry promotes GAGs catabolism in cells. This article provides outcomes analysis of foreign and Russian studies on the efficacy and safety of this medication, and its effect on MPS II patients survivability.